PENGARUH PENDEKATAN KONTEKSTUAL BERSTRATEGI THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA PADA MATERI PERBANDINGAN - Sulastri, Iis; Irawati, Riana; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2017)
The Lack of students 'understanding of the benefits and usefulness of mathematics for their life has become one of the factors causing the low ability of students' mathematical connections. Alternative solutions for this problem is to use a contextual approach with talk think write strategy (TTW) in mathematics. The method used was the method of quasi-experimental design with nonequivalent control group design. The population in this study were all students of 5th grader in SDN Kecamatan Pasirjambu with sample 5th grader A-class students of SDN Cisondari I as a control class and 5th grader B-class as experiment class. Based on the research that has been done, there was a conclusion that : 1) contextual approach to the strategy think talk write (TTW) and conventional learning can improve the ability to connect mathematical students on material ratio, 2) contextual approach to the strategy think talk write (TTW) is better than conventional learning to improve students' mathematical connection to the material ratio, 3) most of the students in the experimental class gave a positive response to the study by using contextual approach with talk think write strategy (TTW).